The Factors Affecting of Baung Fish Proecessing Income in South Labuhanbatu Regency - Wildani Lubis; Nina Maksimiliana Ginting (Faculty of Agriculture Musamus University, 2020)
This study aims to analyze the factors that influence the processing income of Baung fish. Sampling using the census method. The data used are primary and secondary data. Data analysis was performed using multiple linear regression. The coefficient of determination (R2) is 0.90, indicating that the processing income of Baung fish (Y) can be explained by the variables of raw materials (X1), supporting materials (X2), transportation costs (X3), amounting to 90% while the remain 10 % is influenced by other factors that are not included in the equation. The significance value of F is 0,000 indicating that H0 is rejected or H1 is accepted, there are the raw materials variable (X1), supporting materials (X2), transportation costs (X3), which is simultaneously have a significant effect on the variable net income of Baung fish processing (Y). Partially the cost of raw materials has an effect on the income of Baung fish processing, in the other hand the supporting costs and transportation costs partially have no effect on the income of processing Baung fish. The classical assumption test shows that the data is normally distributed, there is no multicollinearity and heteroscedasticity.